81 Getting It Right First Time (GIRFT): Preliminary Results from Incorporation of A Personalised Surgeon Template In Hip Arthroplasty Surgery Documentation. (4th May 2021) - Sandhu, J; Jabr, Y; Sidaginamale, R; Logishetty, R; Cooke, N
Abstract: Introduction: Following the publication of GIRFT guidelines for Total hip replacement operative note documentation produced from analysis of medical negligence claims notified to NHS resolutions by NHS trusts, we reviewed our compliance against the 24 criteria. This was a crucial exercise as inadequate documentation had huge medico-legal consequences and adverse outcome on patient safety. We proposed a pragmatic solution of incorporating prepopulated personalised template into 'Trackcare' system and providing a dedicated desktop installed in surgeon's room for completion of operative notes. Method: We led a team of 4 doctors to review our compliance against 24 criteria laid out by GIRFT. After retrospectively examining 20 operative records from a spread of consultants in the department. A re-audit following incorporation of personalised surgeon templates was conducted to close the loop. Results: Our results showed out of 24 criteria; 8 criteria were met with 80-100% compliance while 15 criteria had <60% compliance. The incorporation of personalised surgeon template has raised compliance to > 90-100% in all 24 criteria. Conclusions: A preliminary review of a single surgeon template has shown that it is simple to use, has excellent compliance, quick to complete the operative notes, advocates patient safety, is user-friendly and is very promising in minimising medico-legal claims for surgeons and the Trust.